Relationship Between The Implementation Of Occupational Health And Safety Manajement Systems With Accident Risk In Fire Fighting Officers - Irmayani, Irmayani; Ginting, Rosita; Samura, Jul; Parinduri, Anggi; Kartika, Vivi (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Fires often come without warning, presenting unexpected risks for firefighters who must remain alert while on duty. This profession is classified as a job that is full of high risks, and the level of risk faced is closely related to the implementation of an occupational health and safety (K3) management system. This research uses a quantitative analytical survey approach with a cross-sectional design to explore the relationship between the implementation of an K3 management system and the risk of accidents among firefighters. In this study, 36 officers were selected as samples using the random sampling method. Primary data was obtained through questionnaires filled out by respondents and assessment sheets prepared by researchers. Data analysis used the chi-square test with a confidence level of 95% (? = 0.05). Rejection of the null hypothesis (Ho) occurs if the p value <0.05, which concludes that there is a significant relationship. Research findings show that as many as 30 field officers (83.3%) are within the scope of the K3 management system which is categorized as poor. There is a significant relationship between the implementation of the K3 management system and the risk of accidents (p=0.000). In order to minimize the risk of work accidents, increasing awareness and discipline of officers in using Personal Protective Equipment (PPE) is very important. It is hoped that the findings from this research can become a basis for related parties to make system improvements and increase the safety of firefighters in the future. Efforts to increase awareness of the importance of K3 and the use of PPE are expected to reduce the risk of accidents and better protect officers as they carry out their duties to protect the public from the dangers of fire.